Teratogenicity study of combination of ginger rhizome extract and noni fruit extract in Wistar rat - Elin Yulinah Sukandar; Atun Qowiyah; Rik Rik Purnamasari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Ginger (Zingiber officinale Roscoe var. sunti Val.) extract in combination with noni (Morinda citrifolia Linn.) extract has been proven to be effective in tuberculosis patients. To examine its safety in pregnancy condition, the influence of combination of ethanol extract of ginger and ethanol extract of noni fruit had been studied in pregnant Wistar rat. The ginger and noni extract were administered orally at dose level combination of 50 and 50 mg/kg BW , 500 and 500 mg/kg BW , 1000 and 1000 mg/kg BW on day sixth to fifteenth of gestation. The mother was sacrified on day nineteenth of gestation to observe life fetus, resorption, and growfail fetus. One third of the fetuses eviscerated for skeletal staining with alizarin red and two third of the fetuses were hardened with Bouin’s fixation solution. No malformation were found in the eviscerated group. The combination at all doses did not cause any fetus resorption, growth failure and did not cause malformation in organ and skeleton. The combination dose of 500 and 500 as well as 1000 and 1000 mg/kg BW caused dark red to black color in the liver of rat fetuses of 7.3 and 8.3 % respectively.Key words: teratogenicity study, Zingiber officinale Roscoe var. sunti Val, Morinda citrifolia Linn.